The Effect of Corporate Social Responsibility (CSR) on Financial Performance in NonFinancial Companies Listed on the IDX - Christine Anna Maria Pakpahan; M. Irsan Nasution; Handriyani Dwilita (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the effect of Corporate Social Responsibility (CSR) on financial performance in non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses an associative quantitative approach with secondary data. Data collection techniques are done through documentation and literature study. The results showed that CSR has no significant effect on Return on Assets (ROA) and Return on Equity (ROE), which indicates that the implementation of CSR programs has not had a direct impact on the efficient use of assets or return on equity. However, CSR has a positive and significant effect on Net Profit Margin (NPM), which indicates that the implementation of CSR is able to increase the company's net profit proportionally to its sales. This finding indicates that CSR has more impact on a company's profitability than efficiency or return on equity.